Detecting and correcting for population structure in genetic case-control studies - Pritchard, Jonathan (Henry Stewart Talks, 2004)
Population structure and false positives in case-control studies of association, Family-based solutions and the TDT, Limitations of family-based solutions, Detecting population structure, Correcting for structure, Structured association and genomic control, Use of unlinked marker loci
Archived at 2021/02/25